Photosynthesis inhibition by exogenously generated singlet oxygen - a note of caution - Hideg, Éva (Acta Biologica Szegediensis, 2008)
Two commonly applied exogenous singlet oxygen sensitizers, rose bengal (RB) and methylene blue (MB) were studied in terms of toxicity and photodynamic efficacy in green leaves. Their effects on photosynthesis with and without the singlet oxygen generating illumination were measured as changes in Photosystem II photochemical yield. Although the two photosensitizers caused the same, concentration-dependent weak inhibition in the dark, RB was more efficient to promote photodynamic injury to Nicotiana tabacum leaves in the presence of visible light. Results show that RB is more advantageous for leaf studies than MB. RB, however, should be used in moderation, as it may cause an additional, singlet oxygen independent inhibition of photosynthesis when applied at high concentrations. The application limit was about 2mM using youngest fully expanded leaves of 4-week-old, green-house grown tobacco plants.